Laser Coherent Combination With Circular Array of Airy Beams - Huahua Wang; Yang Liu; Jian Ma; Qin Wen; Xingwang Kang; Haoran Du; Xinglin Zhong; Fei Chen; Junjie Sun; Lu Gao; Ze Zhang (IEEE Photonics Journal)
A high-efficiency laser coherent combination method based on the virtue of the self-transverse acceleration effect of Airy beams is proposed and demonstrated by converting an array of Gaussian beams into Airy beams array to reduce laser beams separation distance. The coherent combination procedures of circular array for both Airy and Gaussian beams are theoretically and experimentally studied. The results show that the central intensity of the laser coherent combination of the circular array of Airy beams is 14.33 times higher than that of the Gaussian beams array, and the combined efficiency of the circular array of Airy beams is 1.64 times higher than that of the Gaussian beams circular array. The method may provide an efficient way to increase combination efficiency of laser coherent combination array and may have a broad application prospect in optical communication, particle capture, material processing.